A Fungal Diterpene Synthase Is Responsible for Sterol Biosynthesis for Growth - Liu, Yanjie; Duan, Anqing; Chen, Longfei; Wang, Dan; Xie, Qiaohong; Xiang, Biyun; Lin, Yamin; Hao, Xiaoran; Zhu, Xudong (Frontiers in Microbiology, 2020)
A conserved ORF, dps, is described in Pestalotiopsis microspora, sharing remarkable similarity with fungal diterpene synthases whose function is little studied. Loss-of-function approach manifested dps was necessary for growth and development of the fungus. A deletion strain, dpsΔ, showed fundamental retardation in growth which could deliberately be restored by addition of exogenous sterols to the media. GC-MS analysis confirmed loss of the ability to produce certain sterols. Thus, tolerance and resistance of dpsΔ to several stress conditions was impaired. Secondary metabolites such as polyketide derivatives dibenzodioxocinones were significantly diminished. At the molecular level, deletion of dps even affected the expression of genes in mevalonate pathway. This report adds knowledge about fungal diterpene synthases in Pestalitiopsis microspora.